Effective development of the modern economy: problems and prospects - Baranova N. A., Kruglov V. N., Kulakova S. V., Kul'chikova Z. T., Lebedev V. E., Lilimberg S. I., Panina G. V., Vinogradova N. P., Lilimberg S. I., Selezniova T. O., Maer O. I., Malanina A. A., Mfliarenko O. I., Baikova E. I., Minakov A. V., Agapova T. N., Minitaeva A. M., Mishulina O. V., Gorelova N. S., Odinokova T. D., Sokheilinia K., Shpak A. S., Shcherbakova N. S., Tuzandekhdzhani M. (Effective development of the modern economy: problems and prospects, 2025)
the agro-industrial complex is one of the key sectors of the economy, which has significant potential for saturating the domestic market and ensuring food security. In recent years, the republic's agro-industrial complex has demonstrated positive dynamics. For such types of products as bread, potatoes, vegetables and melons, domestic production has almost completely satisfied the population's consumption. However, there remains a dependence on imported poultry meat, vegetable oil, sugar, fruits and berries. Among the main problems that need to be addressed in the republic's agro-industrial complex are dependence on imported plant seeds and breeding material, infrastructure development, increasing the effectiveness of scientific research, timely identification and prevention of internal and external risks based on the use of a system of effective organizational and economic measures.
Keywords: государственная политика; животноводство; продовольственная безопасность; агропромышленный комплекс; урожайность; импорт; экспорт; сельскохозяйственная продукция; food security; import; export; agro-industrial complex; agricultural products; земельные ресурсы; продовольствие; food; валовой сбор; растениеводство; продуктивность скота; продуктивность птицы; экономическая доступность; физическая доступность; land resources; gross harvest; crop yield; livestock productivity; poultry productivity; crop production; livestock farming; economic accessibility; physical accessibility; public policy